Testing a Family Supportive End of Life Care Intervention in a Chinese Neonatal Intensive Care Unit: A Quasi-experimental Study With a Non-randomized Controlled Trial Design - Zhang, Rong; Tang, Qian; Zhu, Li-hui; Peng, Xiao-ming; Zhang, Na; Xiong, Yue-e; Chen, Mu-hua; Chen, Ke-liang; Luo, Dan; Li, Xun; Latour, Jos M. (Frontiers in Pediatrics, 2022)
Background: Neonatal death often occurs in tertiary Neonatal Intensive Care Units (NICUs). In China, end-of-life-care (EOLC) does not always involve parents. Aim: The aim of this study is to evaluate a parent support intervention to integrate parents at the end of life of their infant in the NICU. Methods: A quasi-experimental study using a non-randomized clinical trial design was conducted between May 2020 and September 2021. Participants were infants in an EOLC pathway in the NICU and their parents. Parents were allocated into a family supportive EOLC intervention group or a standard EOLC group based on their wishes. Primary outcomes were depression (Edinburgh Postnatal Depression Scale for mothers; Hamilton Depression rating scale for fathers) and satisfaction. Student t-test for continuous variables and the Chi-square test categorical variables were used in the statistical analysis. Results: In the study period, 62 infants died and 45 infants and 90 parents were enrolled; intervention group 20 infants, standard EOLC group 25 infants. The most common causes of death in both groups were congenital abnormalities (n=20, 44%). Mean gestational age of infants between the family supportive EOLC group and standard EOLC group was 31.45 versus 33.8 weeks (p=0.234). Parents between both groups did not differ in terms of age, delivery of infant, and economic status. In the family support group, higher education levels were observed among mother (p=0.026) and fathers (p=0.020). Both mothers and fathers in the family supportive EOLC group had less depression compared to the standard EOLC groups; mothers (mean 6.90 vs 7.56; p=0.017) and fathers (mean 20.7 vs 23.1; p<0.001). Parents reported higher satisfaction in the family supportive EOLC group (mean 88.9 vs 86.6; p<0.001). Conclusions: Supporting parents in their EOLC pathway in Chinese NICUs might decreased their depression after the death of their infant and increase satisfaction. Further research need to focus on long-term effects and expand on larger populations with different cultural backgrounds.